In-betweeness: the (dis)connection between here and there. The case of Indian student-migrants in Australia - Michiel Baas (Conserveries Mémorielles)
In recent years the number of Indian international students in Australia has increased considerably, from less than four hundred in the early 1990s to close to a hundred thousand by the end of 2009. This phenomenal growth is, to a large extent, due to the fact that a majority of Indian student intends to apply for permanent residency after graduation for which the Australian state had designed clear pathways. As a result education and migration have become highly entangled in Australia. This paper will analyze what it means for young, middle class Indians, to be both students and migrants at the same time. I will do so using the concept of in-betweenness – falling in-between commonly recognized categories – often understood as an ‘accidental state of being’ in literature on migration and transnationalism. I will show, however, that Indian student-migrants very actively seek out this particular state of being as an end goal by itself. As a result this paper will be able to shed light on what – in the Indian case - the (de)coupling of the local and global means, both theoretically and in practice. I will finally make a case against hegemonic ideas of integration which still lean heavily on neoliberal push-and-pull migration models and argue that in order to understand current day migration we need to be open to the possibility that many migrants do not so much seek to integrate themselves in the local but much more into the global.